Islamic Legal Philosophy in a Reinterpretation of Social Justice - Qadriani Arifuddin; Sitti Arfah Mattana; Abdul Aziz; Erwin Saputra; Heryanto Akkas (Mahkota Science Publishers, 2026)
When justice (‘adl) in Islamic law is reduced to a textual adherence devoid of social context, a philosophical reinterpretation becomes imperative. This study aims to reconstruct the concept of social justice in Islamic law through an integrative and critical approach to the philosophy of law. This study employs a qualitative approach with a legal philosophy analysis design that is both normative-critical and interpretative-hermeneutic. The results confirm that the main problem with contemporary Islamic law does not fundamentally lie in the limitations of the norms or the absence of the principle of justice in the sources of sharī‘ah, but rather in an epistemological failure to reinterpret justice as a living, dynamic and contextual social praxis. In empirical reality, Islamic law is often trapped in a legalistic approach that prioritises textual compliance as the primary objective, thereby neglecting the substantive dimension of justice itself. Consequently, the law risks becoming an instrument for legitimising social inequality, particularly when legal interpretation is influenced by patriarchal biases, political interests and economic domination that hinder the protection of vulnerable groups. Therefore, this study emphasises the need for a paradigm shift from a focus on formal compliance towards contextual justice that integrates the maqāṣid al-sharī‘ah, prophetic ethics, and modern theories of social justice within a single transformative framework which not only upholds the normative legitimacy of Islamic law but also ensures its relevance in addressing contemporary issues of injustice.